2018
DOI: 10.1089/ars.2017.7237
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian Sulfur Amino Acid Metabolism: A Nexus Between Redox Regulation, Nutrition, Epigenetics, and Detoxification

Abstract: Increasing the knowledge on transsulfuration outside the liver, understanding the protein-protein interaction networks involving these enzymes, the functional role of their PTMs, or the mechanisms controlling their nucleocytoplasmic shuttling may provide further insights into the pathophysiological implications of this pathway, allowing design of new therapeutic interventions. Antioxid. Redox Signal. 29, 408-452.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 424 publications
0
31
0
1
Order By: Relevance
“…The alterations in chaperone levels, in addition to the impairment in some amino acid's metabolism, such as proline, previously mentioned, and sulfur amino acids [46], due to the low levels of AHCY found in OC cells, could be also indicative of alteration of protein quality. Moreover, impairment in transsulfuration pathways may have consequences in epigenetic modulation of gene expression, glutathione, and taurine synthesis, as well as in proteoglycan sulfation, which is crucial for cartilage and bone homeostasis, and remodeling [47][48][49][50][51][52].…”
Section: Discussionmentioning
confidence: 99%
“…The alterations in chaperone levels, in addition to the impairment in some amino acid's metabolism, such as proline, previously mentioned, and sulfur amino acids [46], due to the low levels of AHCY found in OC cells, could be also indicative of alteration of protein quality. Moreover, impairment in transsulfuration pathways may have consequences in epigenetic modulation of gene expression, glutathione, and taurine synthesis, as well as in proteoglycan sulfation, which is crucial for cartilage and bone homeostasis, and remodeling [47][48][49][50][51][52].…”
Section: Discussionmentioning
confidence: 99%
“…From its side, cysteine can be synthesized within the cell from methionine via transsulfuration pathway 29 . However, previous studies showed that this does not meet the requirements of highly proliferative and/or oxidatively compromised cells (such as cancer cells), which thus, largely rely on the import of this amino acid from the extracellular space 30 . Accordingly, the major transporter for the oxidized form (dominant form in the serum and almost exclusive form in the culture media) of CySH (cystine, CySSCy), known as Xc- system, seems to be consistently up-regulated within different types of cancer 31 – 40 .…”
Section: Ferroptosis—in the Perspectivementioning
confidence: 96%
“…In the liver, a particular metabolic pathway called transsulfuration permits the supply of cysteine by conversion of an essential amino acid: methionine. Yet, this amino acid interconversion is insufficient to provide the cysteine requirements of rapidly dividing cancer cells (4). As mentioned previously, cysteine is a thiol-containing amino acid, which nucleophilicity makes it highly susceptible to redox changes.…”
Section: Cysteine a Key Player In Tumor Metabolismmentioning
confidence: 99%